Upaya Peningkatan Hasil Belajar Peserta Didik Melalui Model Problem Based Learning (PBL) dalam Pembelajaran PAI dan Budi Pekerti Di SD Negeri 06 Tarung-Tarung - Despianti, Despianti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes through the implementation of the Problem Based Learning (PBL) model in Islamic Religious Education (PAI) and Character Education lessons at SD Negeri 06 Tarung-Tarung. The research method used is Classroom Action Research (CAR) based on the Kemmis and Taggart model, which consists of two cycles. Each cycle includes four stages: planning, action implementation, observation, and reflection, which are interrelated in a continuous process. Data were collected through tests and observations, using instruments such as test items to measure student ability and observation sheets to monitor the learning activities. Data analysis techniques involved both qualitative and quantitative descriptive analysis. The results show significant improvement in students' abilities from the pre-cycle to cycle I and II. In the pre-cycle, 35% of students achieved the Minimum Completion Criteria (KKTP), while in cycle I, this increased to 55%, and in cycle II, it reached 90%. The average student learning outcomes also improved from 71.8% in the pre-cycle to 90% in cycle II. Based on these findings, it can be concluded that the implementation of the Problem Based Learning model is effective in improving student learning outcomes in PAI, particularly in the material of the Qur'an Surah Al-Hujurat:13.